2022
DOI: 10.1038/s41467-022-32263-7
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity to COVID-19 mRNA vaccine third dose in people living with HIV

Abstract: In order to investigate safety and immunogenicity of SARS-CoV-2 vaccine third dose in people living with HIV (PLWH), we analyze anti-RBD, microneutralization assay and IFN-γ production in 216 PLWH on ART with advanced disease (CD4 count <200 cell/mm3 and/or previous AIDS) receiving the third dose of a mRNA vaccine (BNT162b2 or mRNA-1273) after a median of 142 days from the second dose. Median age is 54 years, median CD4 nadir 45 cell/mm3 (20–122), 93% HIV-RNA < 50 c/mL. In 68% of PLWH at least one side-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
113
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 54 publications
13
113
2
1
Order By: Relevance
“…In contrast to previous work (Hassold et al, 2022; Nault et al, 2021; Noe et al, 2021; Touizer et al, 2021), we have found no association between the CD4 T cell count and serological outcome, which could be due to insufficient power in this study to detect differences. Moreover, few studies have addressed T cell activity after a third SARS-CoV-2 vaccine dose in this population, but in agreement with our findings a strong boosting effect of a third vaccine dose has been reported regardless of the CD4 T cell count (Vergori et al, 2022). Thus, the lower level of nAbs observed here in PLWH could be in part due to potential differences in boosting of memory responses to enable breadth against Omicron after three vaccine doses.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast to previous work (Hassold et al, 2022; Nault et al, 2021; Noe et al, 2021; Touizer et al, 2021), we have found no association between the CD4 T cell count and serological outcome, which could be due to insufficient power in this study to detect differences. Moreover, few studies have addressed T cell activity after a third SARS-CoV-2 vaccine dose in this population, but in agreement with our findings a strong boosting effect of a third vaccine dose has been reported regardless of the CD4 T cell count (Vergori et al, 2022). Thus, the lower level of nAbs observed here in PLWH could be in part due to potential differences in boosting of memory responses to enable breadth against Omicron after three vaccine doses.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, T cell responses were comparable in the two groups and detectable, even in a small group of PLWH with very poor serological responses, suggesting a potentially important non-redundant immunological role for functional T cells. Overall, our data reinforce the beneficial effect of an additional vaccine dose in boosting adaptive immune responses (Vergori et al, 2022), especially against circulating VOCs in this patient group. Weaker humoral responses were observed in PLWH compared to HIV-negative controls after each dose of vaccine when matched by prior SARS-CoV-2 status.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“… 27 An important concern has been raised about a possible poor functional response to MVA vaccination in people living with HIV, 28 according to previously reported data on vaccines for other viruses, such as influenza, 29 hepatitis B, 30 or even SARS-CoV-2. 31 , 32 Our observation that people living with HIV had a poxvirus-specific T-cell response after natural monkeypox virus infection might suggest a comparable response of people living with HIV also to MVA vaccine, avoiding a differentiated vaccination schedule for this target population.…”
Section: Discussionmentioning
confidence: 98%
“…Longitudinal monitoring of immune responses post-third dose in PLWH is critical to inform the timing of future immunizations in this group. Though some data are available on initial immunogenicity to third COVID-19 vaccine doses in PLWH [14, 15], no studies to our knowledge have assessed the longer-term durability of responses in this population. Furthermore, despite the high incidence of first-time SARS-CoV-2 infections after three vaccine doses, no studies to our knowledge have examined the impact of such infections on responses in PLWH.…”
Section: Introductionmentioning
confidence: 99%